Iso-Wetlands: unlocking wetland ecologies and agriculture in prehistory through sulfur isotopes. Issue 1 (30th December 2022) - Stevens, Rhiannon E.; Reade, Hazel; Read, Daniel S.; Bottrell, Simon H.; Frémondeau, Delphine; Wexler, Sarah
Abstract : page_168 other Iso-Wetlands is a new, NERC-funded collaborative research project involving researchers at UCL Institute of Archaeology, the University of Leeds and the UK Centre for Ecology and Hydrology. The project is developing sulfur isotope analysis of archaeological plants and animals as a new tool for exploring hydrological conditions under which agricultural production was taking place. This development has the potential to improve understanding of water management strategies in the past, particularly in relation to seasonal floodwater agriculture and wetland agriculture (for example, rice paddy systems). The project will open wider possibilities for the use of sulfur isotopes in archaeology and ecology to examine wetland habitat use by both people and animals.